2019
DOI: 10.5222/terh.2019.37880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Anesthesia Method on Mortality and Postoperative Complications in ASA III-IV Graded Geriatric Patients

Abstract: Artan geriatrik ve çoklu morbidite içeren hasta popülasyonu ile ilişkili olarak ASA III-IV grubu hasta operasyonlarında artış görülmektedir. Bu çalışmada preoperatif değerlendirmede ASA III-IV skoru verilen ileri yaş hastalarda uygulanan anestezi tipinin postoperatif komplikasyonlar ve mortalite üzerine etkisinin incelenmesi amaçlandı.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…In addition, studies reporting that the type of anesthesia also affects the rates of morbidity and mortality are available as regional anesthesia causes less mortality compared to general anesthesia [9]. Similarly, Gunturk et al [10] reported a 3.4% mortality rate in patients with regional anesthesia compared to 8.8% in those receiving general anesthesia. In another study in which inhospital mortality rates were compared between patients who underwent regional anesthesia, general anesthesia, and intrasurgery change from general to regional anesthesia (Cv), it was reported that the mortality rate between general and regional anesthesia was 1.38, while it was 2.23 between Cv and regional anesthesia [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies reporting that the type of anesthesia also affects the rates of morbidity and mortality are available as regional anesthesia causes less mortality compared to general anesthesia [9]. Similarly, Gunturk et al [10] reported a 3.4% mortality rate in patients with regional anesthesia compared to 8.8% in those receiving general anesthesia. In another study in which inhospital mortality rates were compared between patients who underwent regional anesthesia, general anesthesia, and intrasurgery change from general to regional anesthesia (Cv), it was reported that the mortality rate between general and regional anesthesia was 1.38, while it was 2.23 between Cv and regional anesthesia [11].…”
Section: Discussionmentioning
confidence: 99%